2019
DOI: 10.1038/s41598-019-40827-9
|View full text |Cite
|
Sign up to set email alerts
|

Interfering with emotional processing resources upon associative threat memory reactivation does not affect memory retention

Abstract: Ample evidence suggests that memories enter a labile state upon retrieval, requiring reconsolidation processes in order to be retained. During this period of instability, various interventions can be applied to modify problematic memories. A novel behavioral intervention was designed, aimed at disrupting amygdala-based cognitive processing following the retrieval of a conditioned threat memory, in order to prevent its reconsolidation. We fear-conditioned participants on day 1, and reactivated their memory on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 60 publications
3
10
0
Order By: Relevance
“…Regarding the putative brain mechanisms underlying our findings, the dlPFC is particularly central to the control of memory retrieval with respect to the actual context, the maintenance and processing of retrieved information in working memory, and the evaluation and monitoring of reactivated memories. At a cognitive level, reconsolidation has been suggested to critically depend on active working memory processing (e.g., rehearsal ll Current Biology 30, 3672-3679, September 21, 2020 3675 Report [30,31], but see also [32]). Accordingly, in the present study, interference with dlPFC activity during the reconsolidation window might have substantially reduced the allocation of working memory resources needed for the re-storage and retention of the destabilized memory, thus leading to disruption of the original memory trace.…”
Section: Reportmentioning
confidence: 99%
“…Regarding the putative brain mechanisms underlying our findings, the dlPFC is particularly central to the control of memory retrieval with respect to the actual context, the maintenance and processing of retrieved information in working memory, and the evaluation and monitoring of reactivated memories. At a cognitive level, reconsolidation has been suggested to critically depend on active working memory processing (e.g., rehearsal ll Current Biology 30, 3672-3679, September 21, 2020 3675 Report [30,31], but see also [32]). Accordingly, in the present study, interference with dlPFC activity during the reconsolidation window might have substantially reduced the allocation of working memory resources needed for the re-storage and retention of the destabilized memory, thus leading to disruption of the original memory trace.…”
Section: Reportmentioning
confidence: 99%
“…A recent study investigated this by employing a threat conditioning paradigm 35 . Following memory reactivation of a conditioned stimulus (CS) that was previously associated with an aversive event (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to earlier studies that typically utilized non-emotional tasks as an intervention (e.g. 1 , 22 26 , 32 , 33 ), the authors 35 instead made use of a cognitively demanding intervention with emotional pictures and neutral faces. As the presentation of emotional stimuli have been shown to increase amygdala activity 37 39 it is possible that their task engaged the amygdala during the critical re-stabilization phase, instead of inhibiting it.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been suggested that administration of propranolol (i.e., a β-adrenergic receptor antagonist) before presenting a fear-conditioned CS can reduce fear responding and its return (Kindt, Soeter, & Vervliet, 2009; but see Schroyens, Beckers, & Kindt, 2017). Similarly, playing Tetris after presentation of a CS has been reported to reduce fear responding (de Voogd, Hermans, & Phelps, 2018;James et al, 2015; but see Chalkia, Vanaken, Fonteyne, & Beckers, 2019). Finally, inserting a break after a single CS-only presentation before continuing with regular extinction training has been reported to reduce return of fear after extinction training (Monfils, Cowansage, Klann, & Ledoux, 2009;Schiller et al 2010; but see Luyten & Beckers, 2017).…”
Section: Reconsolidation Theorymentioning
confidence: 99%